Analisis Potensi Wilayah Dalam Meningkatkan Daya Saing Daerah (Studi Kasus Pada Pemerintah Kabupaten Lumajang) - Mukhammad Iqbal Rakhmatullah (Jurnal Administrasi Publik, 2016)
Abstract: Analysis of The Potency of Region to Local Competitiveness Enhancement (Case Study of The Lumajang Government). The purpose of the research is to find out and analyze economic base sector and regional competitiveness enhancement strategy through the development of economic base sector in Lumajang Regency. By using location quotient (LQ) analysis, shift-share, and typology sectoral can concluded that potential of Lumajang regency is the agricultural sector. Agriculture is the economic base sector its potential rate that was higher than other sectors. The production of this sector has been able to exceed the needs of peoples in their areas. Based on the potential, so strategy of local competitiveness enhancement are the first is the strategy based on the regional competitive superior is performed by reinforcing local innovation system (SIDa), the second strategy is the strategy based on superior comodity through One village one product (OVOP) movement, the third strategy is the unbalanced development strategy performed by developing the industry based on agriculture (agroindustry). Keyword : potency of region, Local Competitiveness Abstrak: Analisis Potensi Wilayah Dalam Meningkatkan Daya Saing Daerah (Studi Kasus Pada Pemerintah Kabupaten Lumajang). Tujuan penelitian ini adalah untuk mengetahui dan menganalisis sektor basis ekonomi dan strategi peningkatan daya saing daerah melalui pengembangan sektor basis ekonomi di kabupaten Lumajang. Dengan menggunakan analisis LQ, Shift-Share, dan Tipologi Sektoral dapat disimpulkan bahwa potensi yang dimiliki kabupaten Lumajang adalah sektor pertanian. Pertanian merupakan sektor basis perekonomian yang tingkat potensialnya paling tinggi diantara sektor-sektor yang lain. Produksi sektor ini juga telah mampu melebihi kebutuhan masyarakat di daerahnya. Berdasarkan potensi tersebut, maka strategi peningkatan daya saing daerah antara lain, pertama adalah strategi berbasis keunggulan kompetitif daerah dilakukan dengan penguatan sistem inovasi daerah (SIDa), strategi kedua dengan strategi berbasis komoditi unggulan melalui gerakan One village one product (OVOP), strategi ketiga dengan strategi pembangunan tidak seimbang yang dilakukan dengan pembangunan industri berbasis pertanian (agroindustry). Kata Kunci : Potensi Wilayah, Daya Saing Daerah